Studi Kasus Gugatan dalam Rekonvensi tentang Pengangkatan Sita Jaminan pada Perkara Perlawanan dalam Putusan Nomor 452/Pdt.G/2023/PA JT - Fauziyah Rahmah Izzati; Linda Rachmainy; Sherly Ayuna Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Reconvention can be filed in all cases except those which regulated in Article 132a HIR. HIR does not regulate material requirements regarding the substantial connection between convention and reconvention claim. Judicial practice tends to do so, as stated in Court Decision Number 452/Pdt.G/2023/PA JT. The Judges determined to reject the reconvention claim based on the consideration that the reconvention’s claim was closely related to the convention one, so the claim in the reconvention was rejected as the convention’s claim decided to be rejected. This research aims to determine the basis of the reconvention claim regarding the removal of collateral confiscation based on the Civil Procedure Law and determine the legal consequence of the court decision which rejected the reconvention claim regarding the collateral confiscation of dispute object. The results showed that the reconvention claim which requested the implementation of the confiscation of collateral is closely related to the convention one. The reconvention filed basically has fulfilled the regulations in Article 132a and Article 132b HIR. The decision to reject this claim was based on the fact that both claims, convention and reconvention, were closely related, this statement is supported by Jurisprudence Number 1527 K/Sip/1973. The legal consequence of rejecting both claims are that the dispute object is not under collateral confiscation status.